Groundwater Occurrence Prediction using Regressions on Morphometric Variables in Upstream Progo Watershed, Yogyakarta - T. Listyani; Budiadi Budiadi (Geological Agency, 2018)
DOI: 10.17014/ijog.5.3.265-276Geomorphological mapping has been done at the upstream part of Progo Drainage Area by measuring some geomorphological indexes and level of shallow groundwater level at 196 stations, to investigate connections between geomorphological characteristics and groundwater system in the area. These indexes are valley floor - height ratio (Vf), valley cross section (Vratio o rVr), stream gradient index (SL), and drainage density (Dd). Based on the linear regression analysis, the four indexes show none to very weak correlation to water table at most locations. It means that all width, height, and width of the river valley do not control shallow groundwater level. However, some locations indicate a strong control of elevation to shallow groundwater level. The first case indicates that there is another controlling factor to the shallow groundwater system. Most likely, a deeper aquifer exists at those locations, which does not show up in the second case. All results give a preliminary indication that morphometry can be used to predict groundwater system in the area.